Phytochemical composition, antiradical and anticholinesterase potentials of Centaurea alba and Centaurea jacea volatile oils - Politeo, Olivera (Array, 2019)
This paper reports on the phytochemical composition as well as antiradical and anticholinesterase potential of volatile oils isolated from Centaurea alba and Centaurea jacea, from Croatia. The volatile components, obtained by hydrodistillation, were determined by GC and GC-MS analyses. A total of 18 compounds were identified in C. alba volatile oil with hexadecanoic acid, germacrene D and tetradecanoic acid as main compounds. A total of 29 compounds were identified in C. jacea volatile oil, with epi-bicyclosesquiphellandrene, aromadendrene and hexadecanoic acid as a major compounds. The tested volatile oils showed low DPPH inhibition potential as well as low to moderate antiAChE potential and low antiBuChE potential.